Узник в маске: роман / Жюльетта Бенцони - Бенцони Жюльетта (ЭКСМО, 2002)
Экземпляры: аб. (20181115) / Инвентарный номер: 58951 / Цена: / Сис.шифр: 84(4Фра)-4 / Авт.знак: Б 46 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)-44